THE NATURE OF WRITTEN TRANSLATION: KEY FEATURES AND CHALLENGES - Khalida Daukaeva, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This article examines the main features of written translation and highlights the specific factors that influence the translation process. Special attention is paid to the differences between written and oral translation, as well as to the challenges translators face when working with different types of texts. The study also discusses strategies and steps that help ensure accuracy, coherence, and equivalence in the target text.